Activity and feasibility of topotecan in the overtreated advanced epithelial ovarian cancer - Korniluk, Jan; Bodnar, Lubomir; Miedzińska-Maciejewska, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2003)
Objective. To determine the activity and feasibility of the topotecan therapy in previously chemo- -overtreated patients with advanced ovarian cancer. Methods. 15 previously overtreated patients with advanced ovarian cancer were given chemotherapy based upon topotecan. Topotecan was infused intravenously for 30 minutes at a dose of 1.5 mg/m2 every day according to 5-day schedule repeated every 21 days. The toxicity profile was noted according to NCI criteria. Results. 15 patients with advanced ovarian cancer were given at least 2 courses of topotecan (median 4, range 2–6). Among the enrolled patients 46% (7/15) were defined as sensitive to cisplatin, 27% (4/15) – resistant and 27% (4/15) – sustained ovarian cancer. We noted the following results: CR (complete response) – 11.1% (1/9), PR (partial response) – 22.2% (2/9), SD (stable disease) – 33.3% (3/9) and PD (progression of disease) - 33.3% (3/9). Time to progression was 4.2 months (median) SD±1.47 (range 2–6). Survival – 7.33 months (median), SD±3.57 (range 3–15). Toxicity profile: 3° and 4° neutropenia according to NCI criteria in 46.6% (7/15) of patients. Anaemia was noted in 66.6% (10/15) of patients and thrombopenia in 33.3% (5/15). Non-haematology toxicity was limited to alopecia that appeared in 53.3% (8/15) of patients. Conclusions. Topotecan seems to be an efficacious drug especially for patients with advanced ovarian cancer that was sustained or overtreated previously. Toxicity profile needs to be monitored carefully and proper medication is necessary when indicated. In advanced overtreated ovarian cancer patients with good performance status topotecan might be useful. Further studies are needed to compare this therapy with other agents used in such fashion.